The effect of potential fall distance on hormonal response in rock climbing. Issue 10 (19th May 2017) - Baláš, Jiří; Giles, David; Chrastinová, Leona; Kárníková, Kateřina; Kodejška, Jan; Hlaváčková, Alžběta; Vomáčko, Ladislav; Draper, Nick
ABSTRACT: The aim of this study was to examine the effect of alterations in potential lead fall distance on the hormonal responses of rock climbers. Nine advanced female climbers completed two routes while clipping all (PRO-all) or half (PRO-½) of the fixed points of protection. Venous blood samples were analysed for total catecholamines, noradrenaline (norepinephrine), adrenaline (epinephrine), dopamine, lactate, cortisol and serotonin. Differences between the two conditions pre, immediately post and 15 min post climbing were assessed using a 2 × 3 repeated measures ANOVA. All hormones and blood lactate concentrations increased significantly ( P  < 0.05) immediately post climb, except for cortisol. Peak cortisol concentrations did not occur until 15 min post ascent. Further, significant interactions between climbing and clipping conditions were found for total catecholamines (890% of basal concentration in PRO-½ vs. 568% in PRO-all), noradrenaline (794% vs. 532%) and dopamine (500% vs. 210%). There were no significant interactions for adrenaline (1920% vs. 1045%), serotonin (150% vs. 127%) or lactate (329% vs. 279%). The study showed a greater catecholamine response with an increase in potential lead fall distance. The most pronounced increases seen in catecholamine concentration were reported for dopamine and noradrenaline.